Synthesis and characterization of poly(3,4-diacetamidostyrene) - (:unkn) unknown (My University, 2009)
0

3,4-Diacetamidostyrene (DAAmS) was synthesized by two step reaction. The first step is the reduction of nitro group of 3-nitro-4-aminostyrene (NAS) to obtain 3,4-diaminostyrene (DAS) which is followed by acylation of amino groups with acetic anhydride as the second step. DAAmS monomer was polymerized by using AIBN as initiator in ethanol solution at 75ºC, for 7 h to reach 87% conversion. Synthesized DAAmS was characterized by FT-IR, GC-MS and NMR (including $^1H$-NMR, APT $^{13}C$ NMR and HETCOR) studies. Poly(3,4-diacetamidostyrene) (PDAAmS) was characterized by FT-IR, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) studies. Disappearance of vinyl absorption peaks in H-NMR spectra of PDAAmS showed the polymerization. Glass transition temperature of polymer was observed to be 174ºC from DSC thermogram.
Keywords: Biyoloji